Energy efficient coordinated multipoint using branch-and-bound and hybrid techniques in LTE-advanced - Mohamed Yusoff, Zainatul Yushaniza (2018)
Over the years, the traditional mobile wireless networks have been focusing mainly on ubiquitous access and large capacity. However, as energy saving and environmental protection become global demands and inevitable trends, researchers and engineers have shifted their focus to energy-efficiency-oriented design, which is an important element for designing green communication systems. Long Term Evolution-Advanced (LTE-A) is one of the mobile networks affected by this new design paradigm. In line of this, LTE-A via 3GPP Standard Release 10 has introduced the concept of coordinated multipoint (CoMP) for both uplink and downlink transmission. CoMP is one of the new technologies introduced in LTE-A which helps to achieve the requirements of 4G issued by International Telecommunication Unit (ITU). At the same time, it is also one of the techniques for Inter-cell Interference Coordination (ICIC) that assists to eliminate the interference caused by neighbouring base stations. In addition, CoMP is also able to improve the channel capacity of the system. It can be implement for user who experiencing weak signals especially user at the cell-edge because CoMP will coordinate several base stations for data transmission. However, there are some challenges that CoMP technique faced and one of them is on its energy efficiency. The main aim of this thesis is to analyze the energy efficiency performance of CoMP and non-CoMP technique, as well as to enhance the energy efficiency performance of CoMP by using branch and bound also hybrid technique. While branch and bound focuses on optimizing the design parameter of coordinated scheduling /coordinated beamforming (CoMP-CS/CB), the hybrid CoMP combines the advantages of both CoMP-CS/CB and coordinated multipoint joint transmission (CoMP-JT). This thesis focuses on downlink part only. Several important aspects related to energy efficiency and power consumption of CoMP have been considered such as transmit power, base stations or power and backhaul power. To apply the CoMP-JT and CoMP-CS/CB techniques, it is depending on the coordination ap- proach of data transmission and signalling from multiple base stations. CoMP-JT coordinates the transmission from a number of base stations and send them to the receiver. On the other hand, CoMP-CS/CB use several base stations for scheduling the data, but the transmission of data and signalling only involve a base station point. From these two techniques CoMP-JT system offers better quality of service performance and energy efficiency but lacks of the significant backhaul problem which hampered its implementation in the real world. Therefore, CoMP-CS/CB can be regard as a better solution despite its energy efficiency limitation. A generic analytical equation for CoMP is formulated and later is used for analyzing the energy efficiency of CoMP-JT and CoMP-CS/CB. Owing to the analysis, the proposed branch and bound method provides a sophisticated solution with more than 41.62% improvement compared to the standard CoMP-CS/CB, while CoMP-hybrid produce the output 7.74% different between CoMP-JT.